TAXONOMIA E RELAÇÕES FILOGENÉTICAS DE Phalocallis HERB. (IRIDACEAE-IRIDOIDEAE) - FERREIRA, DAIANE GONÇALVES (2021)
Phalocallis Herb belongs to the family Iridaceae, subfamily Iridoideae, tribe Tigridieae. It is formed by herbaceous plants, with purplish to bluish violet flowers, with brown spots and yellow stains. Phalocallis is represented by three species with distribution in South America, Phalocallis coelestis (Lehm) Ravenna, Phalocallis geniculata (Klatt) Ravenna and Phalocallis oreophila (Speg.) Ravenna. The genus has a long taxonomic history, still with divergences regarding the delimitation and validation of the species. The objective of this study is to provide data to elucidate questions regarding the taxonomy of Phalocallis using different methodological approaches. For this, a morphological characterization of the genus was carried out, in addition to the floral anatomy, leaf anatomy and description of pollen grains. Phylogenetic analyzes were also performed using two plastid markers. A review of the recognized species, their distribution maps, illustrations and identification key is presented. The present study resulted in the description of a new species belonging to the genus, which is possibly already threatened with extinction. The morphological and anatomical data revealed some novelties for the genus, such as the presence of papillae on the leaf and of secretory tissue in the anther connective region, indicating that the genus offers three resources to the pollinator. Structural differences were also observed in the anther region, in addition to the pollen grains, which showed differences in the size and pattern of the exine, demonstrating that the anatomical characters may contribute to the taxonomy of the group.